Occupation, Organisation, Opportunity, and Oversight: Law Firm Client Accounts and (Anti-)Money Laundering - Benson, Katie (European journal on criminal policy and research, 2024)
The misuse of law firm pooled client accounts has been identified as one of the primary areas of money laundering and terrorist financing risk for the legal profession. This article demonstrates the varied role that client accounts can play in money laundering, through both purposeful exploitation (by the predicate offender, the lawyer/law firm, or both) of the client account or of other legitimate business processes in which the client account inevitably plays a role, and/or a failure to fulfil regulatory requirements. It examines how the nature of law firm pooled client accounts in the UK creates and shapes an ‘opportunity structure’ for money laundering, and the occupational and organisational context of this opportunity structure. The article argues that examining the opportunity structures created by client accounts is a more useful approach than categorising them as inherently low, medium or high risk, as is seen in many national risk assessments and reports. Identifying the factors that create opportunities for money laundering through law firm client accounts can direct policymakers striving to prevent money laundering in the legal profession towards more targeted oversight mechanisms.